Programa de preparação de planos de vida para a aposentadoria: avaliação de necessidades, processo e efeitos - Nunes, Cristiane Oliveira Alves Telles (2015)
As life expectancy increases, retirement is lasting for a much longer period of time, making it necessary to better understand and to discover how to manage the psychological issues associated with this phenomenon. One contribution that is needed is the development of theoretically-grounded interventions that enable pre-retirees prepare life plans that will help them satisfy their post-career needs. A systematic literature review of Brazilian studies was conducted, to understand prevailing thoughts about retirement preparation programs (RPPs) and examine existing evidence about the effects of RPPs, offered in Brazil. The results indicate that many RPP coordinators invite speakers to talk about issues that affect people’s wellbeing in the post-retirement period, but researchers do not seem to build on programs developed by others or report assessing the effects of these programs. As such, the objectives of this study were to: (a) assess pre-retirees’ needs, (b) evaluate indicators of the validity and social acceptance of the intervention program, and (c) evaluate the effects of the RPP on the quality of the participants’ plans and their social skills repertoire. Using a quasi-experimental research design, 23 pre-retirees (average age of 53 years) were divided between the Intervention Group (IG; n = 10), and the Comparison Group (CG; n = 13). Interviews were conducted with the IG members, to assess their retirement planning needs. The participants were assessed before and after the intervention program and in a follow-up evaluation, using the Retirement Life-Plans Register and the Social Skills Inventory for the Elderly, along with complementary instruments to evaluate the intervention program, including: a Session Assessment, an Intervention-Program Assessment, and a field diary. The intervention was conducted with the IG participants; the CG participants had the opportunity to attend a session on preparing for retirement, after the posttest. The qualitative data were analyzed using content analysis techniques and the quantitative data were analyzed using descriptive and inferential methods (nonparametric tests). The needs assessment led to the identification of the following demands: the significance of retirement, financial planning, relationships, social skills, coping skills, use of free time, quality of life, and planning skills. The program, conducted in group format, involved eight weekly, two-hour sessions, using strategies such as informative presentations, discussions, group dynamics, and homework assignments. The results of the process-evaluation indicated strong social acceptance of the program (high attendance, completion of homework assignments, engagement in the proposed activities, and satisfaction with the sessions) and program implementation integrity. The effects-assessment indicated that the RPP improved the quality of the IG participants’ retirement life plans and their social skills repertoire, when compared with the CG, on both the posttest and follow-up assessments. In conclusion, this study models an approach that is theoretically-grounded, informed by previous interventions, needs-based, of moderate length, and able to improve the quality of the participants’ retirement plans and social skills, although the program does not address all the needs of pre-retirees, reported in the research literature. In future studies, the program should be evaluated with a larger number of participants and with people from other regions of the country.